Feasibility of allogeneic mesenchymal stem cells in pediatric hypoxic-ischemic encephalopathy: Phase I study - AKKOÇ, TUNÇ (BAISHIDENG PUBLISHING GROUP INC, 2021)
BACKGROUND Hypoxic-ischemic encephalopathy (HIE) is one of the leading causes of death and long-term neurological impairment in the pediatric population. Despite a limited number of treatments to cure HIE, stem cell therapies appear to be a potential treatment option for brain injury resulting from HIE. AIM To investigate the efficacy and safety of stem cell-based therapies in pediatric patients with HIE. METHODS The study inclusion criteria were determined as the presence of substantial deficit and disability caused by HIE. Wharton's jelly-derived mesenchymal stem cells (WJ-MSCs) were intrathecally ( IT), intramuscularly (IM), and intravenously administered to participants at a dose of 1 x 10(6)/kg for each administration route twice monthly for 2 mo. In different follow-up durations, the effect of WJ-MSCs administration on HIE, the quality of life, prognosis of patients, and side effects were investigated, and patients were evaluated for neurological, cognitive functions, and spasticity using the Wee Functional Independence Measure (Wee FIM) Scale and Modified Ashworth (MA) Scale. RESULTS For all participants (n = 6), the mean duration of exposure to hypoxia was 39.17 + 18.82 min, the mean time interval after HIE was 21.83 +/- 26.60 mo, the mean baseline Wee FIM scale score was 13.5 +/- 0.55, and the mean baseline MA scale score was 35 +/- 9.08. Three patients developed only early complications such as low-grade fever, mild headache associated with IT injection, and muscle pain associated with IM injection, all of which were transient and disappeared within 24 h. The treatment was evaluated to be safe and effective as demonstrated by magnetic resonance imaging examinations, electroencephalographies, laboratory tests, and neurological and functional scores of patients. Patients exhibited significant improvements in all neurological functions through a 12-mo follow-up. The mean Wee FIM scale score of participants increased from 13.5 +/- 0.55 to 15.17 +/- 1.6 points (mean +/- SD) at 1 mo (z = - 1.826, P = 0.068) and to 23.5 +/- 3.39 points at 12 mo (z = -2.207, P = 0.027) post-treatment. The percentage of patients who achieved an excellent functional improvement (Wee FIM scale total score = 126) increased from 10.71% (at baseline) to 12.03% at 1 mo and to 18.65% at 12 mo post-treatment. CONCLUSION Both the triple-route and multiple WJ-MSC implantations were safe and effective in pediatric patients with HIE with significant neurological and functional improvements. The results of this study support conducting further randomized, placebo-controlled studies on this treatment in the pediatric population.
Keywords: Hypoxic-ischemic encephalopathy; Pediatric; Stem cell; Wharton jelly; FUNCTIONAL RECOVERY; TRANSPLANTATION; THERAPIES; CAPACITY; STROKE; RAT